CATCH PRODUCTION FACTOR ANALYSIS BOAT CHART CATCHING EQUIPMENT AT PPP CAROCOK TARUSAN SOUTH COASTAL DISTRICT, WEST SUMATRA PROVINCE - Nur akmaliatulkomariah; Bustari Bustari; Jonny Zain Jonny Zain (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2021)
ABSTRACTFactors of production are a unit needed to carry out fishing business activities. Production factors play a role in the success of the fishing gear operation for the lift net. The purpose of this study was to determine the factors that influence the number of catches on the boat lift fishing gear operated by fishermen based at the Carocok Tarusan Coastal Fishing Port. The method used is a survey method. The data collected is data on catches for 3 years obtained from the boat logbook of the boat chart. The data collected were tested using multicollinearity (independent test). Subsequently, multiple regression analysis was performed. The relationship of production factors to the catch of the boat lift fleet is in the form of the equation Y= -699,234 + 46,158X1- 11.808X2+ 34,530X3+120X4 where is X1 is the number of fishermen, X2 long at sea, X3 number of lamps and X4 wide mouth waring.Keywords: Boat chart, factors of production, multiple linear regression, South